EMOTIONAL VALUE, SOCIAL VALUE, CONNECTEDNESS DAN SATISFACTION TERHADAP REPURCHASE INTENTION PADA MERCHANDISE DAN RILISAN FISIK BAND HARDCORE - Muchammad Ilham Ferdiansyah; Okto Aditya Suryawirawan (Jurnal Ekonomi Dan Bisnis, 2024)
This research aimed to find out the effect of emotional value, social value, connectedness, and satisfaction on the consumers' repurchasing intentions of merchandise and physical releases of hardcore bands. The research was quantitative. Furthermore, the data collection technique was a non-probability sampling. In line with that, there were 97 respondents as the sample. The instrument in the data collection technique was a questionnaire. The questionnaires were distributed to the respondents. Moreover, the data analysis technique used multiple linear regressions with SPSS (Statistical Product and Service Solution). The result of the classical assumption test showed that there were not any fraud variables. Additionally, the result indicated that both social value and satisfaction had a positive and significant effect on the consumers' repurchasing intention of merchandise and physical releases of hardcore bands. However, emotional value as well as connectedness had a positive but insignificant effect on the consumers' repurchasing intention of merchandise and physical releases of hardcore bands.